2001
DOI: 10.1002/dvdy.1196
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular ATP receptor, cP2Y1, inhibits cartilage formation in micromass cultures of chick limb mesenchyme

Abstract: We have investigated the function of the G protein-coupled receptor for extracellular ATP, chick P2Y 1 (cP2Y 1 ) during development of the chick limb. cP2Y 1 is strongly expressed in undifferentiated limb mesenchyme cells but appears to be lost from cells as they differentiate, raising the possibility that the function of this receptor may be to inhibit cell differentiation. This pattern of expression was particularly striking surrounding areas of cartilage formation. We tested whether cP2Y 1 was able to regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…ATP has been reported to inhibit cartilage formation in micromass cultures (Meyer et al, 2001), promote proteoglycan breakdown and glycosaminoglycan release in bovine nasal cartilage (Brown et al, 1997) and increase the production of inflammatory mediators, nitric oxide (NO) and PGE2 (Varani et al, 2008b). Furthermore, P2Y2…”
Section: Functional Effects Of P2 Receptor Signalling In Chondrocytesmentioning
confidence: 99%
“…ATP has been reported to inhibit cartilage formation in micromass cultures (Meyer et al, 2001), promote proteoglycan breakdown and glycosaminoglycan release in bovine nasal cartilage (Brown et al, 1997) and increase the production of inflammatory mediators, nitric oxide (NO) and PGE2 (Varani et al, 2008b). Furthermore, P2Y2…”
Section: Functional Effects Of P2 Receptor Signalling In Chondrocytesmentioning
confidence: 99%
“…It is known that PPADS is not only relatively selective for P2X receptors but can also antagonize P2Y 1 receptor activity (Ralevic & Burnstock 1998). As P2Y 1 activity inhibits chondrogenic differentiation (Meyer et al 2001), PPADS may stimulate type II collagen synthesis by suppressing the negative effect of P2Y 1 activity on chondrogenic differentiation.…”
Section: Role Of P2x 4 Receptor In Chondrogenesismentioning
confidence: 99%
“…Earlier we reported that this receptor contributed to the elevation of cytosolic Ca 2+ levels of chondrogenic cells on day 3 of culturing [73]. The apparent discrepancy between these studies may be explained by the fact that whilst Meyer and colleagues used cultures established from mesenchymal cells derived from the forelimbs only [95], the micromass cultures used in our study were of mixed origin containing progenitor cells from both fore and hind limb buds [74]. It has long been known that chondrogenesis in HDC derived from wing and leg precartilage cells is affected differently by certain morphogens such as transforming growth factor-β1 (TGF-β1) or retinoic acid, and they also differ from each other in condensation morphology and organisation of fibronectin during the early phase of differentiation [96].…”
Section: P2 Purinergic Receptor Expression and Function During Chondrmentioning
confidence: 95%
“…The first study on the involvement of purinergic signalling in chondrogenesis in vitro showed that ATP acting on the P2Y 1 receptor inhibited cartilage formation in HDCs of embryonic chick limb bud-derived mesenchymal cells [95]. In contrast, our group has reported that cells in HDC responded to extracellular ATP by elevating their intracellular Ca 2+ levels mainly at the time of chondroblast formation and administration of ATP to the culture medium stimulated chondrogenesis [74].…”
Section: P2 Purinergic Receptor Expression and Function During Chondrmentioning
confidence: 97%